Fun and Exciting Research in Competitive Research Design - Kadarwati, Sri; Sumarni, Woro; Wijaya, Atika; Alauhdin, Mohammad; Kurniawan, Cepi; Huda, Nuril; Budiyanto, Teguh; Pramestia, Rena Aliya; Azzahra, Elvara Siti (Universitas Negeri Semarang, 2023)
Research involving high school students or equivalent has been in great demand in recent years. Various ministries , government institutions and universities have launched various competitive research programs and events competition based research for SMA/MA level. Students and teachers at MAN 1 Semarang City have so far experienced many difficulties in designing competitive research. The achievements made by MAN 1 Semarang City students in the field of research are still very limited. The limited research experience of accompanying teachers could also be one of the causes. Collaboration with universities as institutions that not only provide education and teaching, but also research development, is a must. Therefore, assistance in designing research that is worthy of being competed in prestigious research competitions by the Semarang State University community service team is very important. Mentoring activities are carried out in the fields of science, technology and social humanities, involving Semarang State University research experts from both fields of study. This activity involved 31 students from MAN 1 Semarang City who were members of the madrasa research program along with 9 research assistant teachers from various fields of science. Activities include assistance in several phases of competitive research design, namely creating research ideas, drafting and finalizing research designs. This activity received a very good response and was seen as being able to help students and research assistant teachers at MAN 1 Semarang City in generating brilliant research ideas with novelty or novelty and high usefulness for the advancement of science and technology. A total of three proposal titles were produced from this activity ; one title in the field of social and human affairs and two titles in the field of science and technology. The obstacles in implementing mentoring are felt by teachers and students who have to spare time between busy teaching and learning activities at madrasas. The implementing team expressed its appreciation to the research supervisors and students who had successfully prepared research proposals to the final stage.